2019
DOI: 10.1002/app.48859
|View full text |Cite
|
Sign up to set email alerts
|

High‐strength functionalized pectin/fibroin hydrogel with tunable properties: A structure–property relationship study

Abstract: Hydrogels possessing high mechanical strength and well-controlled properties are of utmost interest in bone tissue engineering. In the current study, a strong self-crosslinked hydrogel with variable properties has been developed from a combinatory composition of functionalized pectin and silk fibroin. Pectin chains underwent partial oxidation to be decorated with aldehyde functionalities. Later on, functionalized polysaccharide and protein were blended with different ratios, and corresponding variations in cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…Many synthetic polymers and natural derivative materials can be used to synthesize hydrogels [ 21 , 23 ]. By modifying the method and degree of cross-linking, the degradation rate, porosity, and mechanical properties can be easily controlled [ 24 ]. The hydrogel prepared by combining natural polymer, synthetic polymer, and HA has achieved good results in bone repair experiments [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many synthetic polymers and natural derivative materials can be used to synthesize hydrogels [ 21 , 23 ]. By modifying the method and degree of cross-linking, the degradation rate, porosity, and mechanical properties can be easily controlled [ 24 ]. The hydrogel prepared by combining natural polymer, synthetic polymer, and HA has achieved good results in bone repair experiments [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, any changes occurring in the material are reversible, even though such behavior is atypical in chemical hydrogels. Nevertheless, Khorsidi et al [53] have found a growing number of aminealdehyde cross-links to correlate with the increased shear-thinning character of hydrogels. Another research found that similar material compositions to the ones examined in the current study can be printed by microextrusion; therefore, a certain level of shear-thinning behavior can be assumed [54].…”
Section: Rheologymentioning
confidence: 99%
“…Сопоставлять следует константы k D1 и k D2 между собой (характер взаимодействия с адсорбционными центрами одинаков), а также величину соотно-шения констант для разных субстратов. Для группы тканевых пектинов величина относительного показателя примерно одинакова (1,26). Для P MIGR соотношение констант возросло до 2,04, что свидетельствует одновременно об отсутствии препятствий для поддержания градиента концентрации сорбата в поверхностном слое и о повышенном сопротивлении для протекания внутридиффузионных процессов.…”
Section: анализ диффузионных моделей переноса теофеллина в коллоидной системе пектинов льнаunclassified
“…Наряду с традиционными сферами применения биополимера в пищевой и фармацевтической промышленности растет интерес к использованию его способности к различным видам взаимодействий для получения новых функционализированных материалов. В частности, разработка специальных методов модификации обеспечивает получение самосшитых гидрогелей пектина с фиброином шелка, обладающих высокой механической прочностью и переменными свойствами, которые представляют интерес в инженерии костной ткани [1]. Управление структурной организацией гидрогелей пектина с хитозаном и нанокристаллической целлюлозой позволяет получать биофункциональные инъекционные материалы для тканевой инженерии [2].…”
Section: Introductionunclassified